The Formation Design of Noise Reducers from Plywood, Foam, Tray, dan Coconut Fiber for Static Sources - Fachrul, Melati Ferianita; Yulyanto, Wisnu Eka; Merya, Asharani (Makara Journal of Technology, 2011)
The Formation Design of Noise Reducers from Plywood, Foam, Tray, dan Coconut Fiber for Static Sources. Research was conducted in a semi-anechoic room using a method referring to the ISO 3745. The design used is the Hemisphere in which the source of noise is analogous to engines in an industry. The value reduction in the rate of sound power is obtained by comparing the sound power level before and after control is given. The noise control test materials used consist of layers of plywood, foam, fiber and tray (egg box). The effectiveness of these materials is tested by measuring the sound transmission loss (STL). Test results reveal that the sound power level (Lw) of the source of noise produces a high Lw which is 99.6 dB. at a frequency of 8000 Hz. The measurement of Lw on the source of noise which is covered by plywood produces a total of 78.66 dB Lw with an Lw reduction of 21.02%. The measurement on the sound source covered by plywood and foam materials produces a total of 47.79 dB Lw with an Lw reduction of 52.02%. The measurement of Lw by combining plywood, foam, and tray produces a total of 33.02 dB Lw with an Lw reduction of 66.84%. The measurement of the total Lw after being covered by plywood, foam, fiber, and tray is a total of 31.94 Lw dB with an Lw reduction of 67.93%.